Machiavellianisme, Kecerdasan Emosional, Locus of Control, serta Pengaruhnya terhadap Perilaku Etis Auditor - Martadi, Indiana Farid; Soemantri, Roebiandini; Harahap, Devianti Yunita (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This research was conducted based on the phenomenon of unethical behavior carried out by BPK auditors which resulted in reducing public trust to the independence, integrity, and professionalism of BPK auditors. The aim of this research is to determine the influence of machiavellianism and emotional intelligence on auditors’ ethical behavior, as well as to determine the role of locus of control in moderating the influence of machiavellianism and emotional intelligence on auditors’ ethical behavior. This research uses a quantitative method with a survey approach to all audit units both at the head office and the BPK Provincial Representative Offices in Indonesia. This research uses primary data by completing online questionnaire by 241 respondents from middle level auditor to high level auditor. Hypothesis testing uses the SEM-PLS analysis tool. The results of the study show that machiavellianism has a negative influence, emotional intelligence has a positive influence on auditors’ ethical behavior. Meanwhile, internal locus of control and external locus of control cannot moderate the influence of machiavellianism and emotional intelligence on auditors’ ethical behavior.